2022
DOI: 10.1021/acssuschemeng.2c01469
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Valorization of E-Waste Plastic through Catalytic Pyrolysis Using CO2

Abstract: A massive amount of waste of electrical and electronic equipment (E-waste) is being discarded as a solid waste. A valorization platform for the organic part in E-waste has not been fully matured, while metallic compounds have been properly recycled. In these respects, a reliable disposal platform for complex plastic compounds in E-waste is developed in this study. Using a pyrolysis platform, the complicated plastic mixture in E-waste was valorized into value-added products. To deliberate a more environmentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For example, monitor waste contains a multilayered plastic composition of high-impact polystyrene, poly(methyl methacrylate), and acrylonitrile butadiene styrene, PET, and polycarbonate (PC: 2.2%). 88 Plastic oil from monitor waste pyrolysis contained more than 50 chemical species, including a large quantity of methyl methacrylate, benzene derivatives, PAHs, and bisphenol A. Since this complicated chemical mixture is not suitable for industrial applications, it is suggested to convert it into value-added syngas.…”
Section: Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, monitor waste contains a multilayered plastic composition of high-impact polystyrene, poly(methyl methacrylate), and acrylonitrile butadiene styrene, PET, and polycarbonate (PC: 2.2%). 88 Plastic oil from monitor waste pyrolysis contained more than 50 chemical species, including a large quantity of methyl methacrylate, benzene derivatives, PAHs, and bisphenol A. Since this complicated chemical mixture is not suitable for industrial applications, it is suggested to convert it into value-added syngas.…”
Section: Catalystmentioning
confidence: 99%
“…Since this complicated chemical mixture is not suitable for industrial applications, it is suggested to convert it into value-added syngas. 88 Product distribution between plastic oil and gas from pyrolysis of PE/PP/PS/PET mixture is highly dependent on the pyrolysis temperature 73,74 and heating rate. 70 As the pyrolysis temperature and the heating rate increased, the yield of pyrolysis gas also increased.…”
Section: Catalystmentioning
confidence: 99%
“…It has been reported that as much as 3.5 tons of CO 2 can be emitted into the atmosphere per ton of plastic incinerated. 15,16 Flame retardants are added to polymers to enhance their ability to resist combustion. Containing mainly phosphorus or halogenated compounds, they are added to plastic components near and around electrical wires, cables, and other sensitive equipment to ensure their safe usage.…”
Section: Introductionmentioning
confidence: 99%
“…When landfilled, the heavy metals as well as flame retardants commonly added to E-waste plastics often leach into the local environment, polluting the soil, water sources, and eventually the food chain. ,, When incinerated for energy conversion, large amounts of CO 2 are released into the atmosphere, contributing to the ongoing global warming climate crisis. It has been reported that as much as 3.5 tons of CO 2 can be emitted into the atmosphere per ton of plastic incinerated. , …”
Section: Introductionmentioning
confidence: 99%
“…Energy and exergy efficiencies of this system are 51.75% and 45.22%, respectively. Jung et al 19 devised a reliable platform for treatment of complex plastic compounds in e-waste, which was used for catalytic pyrolysis of LCD monitor waste with a nickel catalyst to promote H 2 formation. Chari et al 20 calculated the climate change impact of −371 kg CO 2 per ton of mixed plastic wastes processed by hydrogen production process.…”
mentioning
confidence: 99%